2017
DOI: 10.1215/08992363-3749069
|View full text |Cite
|
Sign up to set email alerts
|

Killers: Orcas and Their Followers

Abstract: Orcas are among the world’s most charismatic animals, combining grace and power, violent when they need to be, but rarely toward humans and never in the wild. Attacks on humans have been restricted to captive orcas, opening up widespread discussions on the ethics of marine-mammal captivity and prompting major changes to the North American orca-display industry, as represented by corporate giants such as SeaWorld. Orcas are now more likely to be followed online than watched either in captivity or in the wild, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This influence is supported in the results of a recent survey, which showed that 73% of the US public learned about killer whales via the media ( Edge Research, 2014 ). It is also reflected in the dramatic fall in the stock market value of North America’s primary provider of killer whale attractions, which has been blamed on negative publicity and resultant decreasing visitor numbers ( Peterson, 2014 ; Huggan, 2017 ). In 2016, the same provider announced the end of their captive breeding programme and therefore the eventual end of captive killer whale shows at their attractions ( Hacket, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This influence is supported in the results of a recent survey, which showed that 73% of the US public learned about killer whales via the media ( Edge Research, 2014 ). It is also reflected in the dramatic fall in the stock market value of North America’s primary provider of killer whale attractions, which has been blamed on negative publicity and resultant decreasing visitor numbers ( Peterson, 2014 ; Huggan, 2017 ). In 2016, the same provider announced the end of their captive breeding programme and therefore the eventual end of captive killer whale shows at their attractions ( Hacket, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the qualitative responses, media influence was cited less frequently for SWTD attractions as a factor in potential visitation. The showing of Blackfish on well-watched television outlets is credited for broadening the media profile of the negative issues associated with MMP killer whale shows, especially given the deaths of trainers highlighted in the film ( Huggan, 2017 ; Parsons & Rose, 2018 ).…”
Section: Discussionmentioning
confidence: 99%